2019
DOI: 10.1016/j.suronc.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Involved margins after lumpectomy for breast cancer: Always to be re-excised?

Abstract: Background: The oncologic benefit of upfront re-excision of involved margins after breastconserving surgery in the context of current multimodal clinical management of breast cancer is unclear. The aim of the present study was to assess the 5-years locoregional recurrence (LRR)-free and distant metastases (DM)-free survival probabilities in patients not undergoing re-excision of positive margins after lumpectomy for breast cancer. Methods: A cohort of 104 patients with positive margins not undergoing re-excisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The rate of residual disease in our study falls in the lower limit of previous reports having a rate between 28.2% and 62.7%. 16,19,22,27,28 no difference regarding the loco-regional recurrence and metastasis rates between control patients with clear margins after the first surgery and the patients who refused a secondary surgery despite having positive margins. 22 Vos et al found that the combination of omitting re-excision and addition of a whole-breast irradiation do not lower disease-free survival and overall survival in patients with focally positive margins from the primary lumpectomy, although omitting re-excision can increase the rates of ipsilateral tumor recurrence.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The rate of residual disease in our study falls in the lower limit of previous reports having a rate between 28.2% and 62.7%. 16,19,22,27,28 no difference regarding the loco-regional recurrence and metastasis rates between control patients with clear margins after the first surgery and the patients who refused a secondary surgery despite having positive margins. 22 Vos et al found that the combination of omitting re-excision and addition of a whole-breast irradiation do not lower disease-free survival and overall survival in patients with focally positive margins from the primary lumpectomy, although omitting re-excision can increase the rates of ipsilateral tumor recurrence.…”
Section: Discussionmentioning
confidence: 97%
“…16,19,22,27,28 no difference regarding the loco-regional recurrence and metastasis rates between control patients with clear margins after the first surgery and the patients who refused a secondary surgery despite having positive margins. 22 Vos et al found that the combination of omitting re-excision and addition of a whole-breast irradiation do not lower disease-free survival and overall survival in patients with focally positive margins from the primary lumpectomy, although omitting re-excision can increase the rates of ipsilateral tumor recurrence. 24 In another study by Fisher et al, they described that breast cancer-related death was not influenced by re-excision compared to the group with no further re-excision after quadrantectomy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…12 Some studies estimate that 20% to 50% of patients return to the operating room for positive or inadequate margins. 13,14 The economic cost is significant with one group demonstrating that return to the operating room for re-excision will result in nearly an 85% increase in cost per patient. 15 Even more importantly, inadequate surgical resection results in emotional and psychological strain for the individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…While studies have demonstrated that re-excision for breast conservation does not influence the overall survival of patients [ 23 24 ], the oncologic benefit of re-excision for positive resection margins remains unclear. Based on a propensity score matching analysis of 2,110 patients, Sorrentino et al [ 25 ] reported no significant benefit in local control with re-excision. However, this finding differs from that of Vos et al [ 24 ], who reported a significantly high risk of IBTR with the omission of re-excision in patients with positive margins.…”
Section: Discussionmentioning
confidence: 99%